Wickerhamiella kiyanii f.a., sp nov and Wickerhamiella fructicola f.a., sp nov., two yeasts isolated from native plants of Atlantic rainforest in Brazil - Dayo-Owoyemi, Ifeloju [UNESP]; Rosa, Carlos Augusto; Rodrigues, Andre [UNESP]; Pagnocca, Fernando Carlos [UNESP] (Soc General Microbiology, 2014)
Two novel species, Wickerhamiella kiyanii f.a., sp. nov. (type strain FB1-1DASP(T)=CBS 12905(T)=CBMAI 1613(T)) and Wickerhamiella fructicola f.a., sp. nov. (type strain H10Y(T)=CBS 12902(T)=CBMAI 1614(T)) are proposed in the Wickerhamiella clade (Saccharomycetes, Saccharomycetales) to accommodate three strains isolated from flowers and fruits typical of the Brazilian Atlantic rainforest. The novel status of these yeast species was established by sequence divergence observed in the D1/D2 domains of the LSU rRNA gene from the most closely related, described species as well as by phylogenetic analysis. Wickerhamiella kiyanii sp. nov. differs from its nearest phylogenetic neighbours W. pagnoccae CBS 12178(T), Candida jalapaonensis CBS 10935(T) and Candida drosophilae CBS 8459(T) by 2.2-4.2 % in the D1/D2 sequences. By contrast, a sequence divergence of 13.2-13.8% was observed between W. fructicola sp. nov. and its closest, described phylogenetic relative Candida kazoui JCM 12558(T) and Candida hasegawae JCM 12559(T). Taxonomic descriptions of the two novel species are given.